Audit Quality: Do the Audit Committee and Internal Audit Arrangements Matter? - Zain, M.; Abdul Wahab, Effiezal Aswadi; Boon, F. (Virtus Interpress, 2010)
This study examines the impact of corporate governance mechanisms namely audit committee characteristics, internal audit arrangements, and managerial ownership on external audit fees. Using a sample of 539 firms listed on the main board, the results of the study document a positive relationship between audit committee independence and audit fees. Consistent with the capital reputational theory, the result suggests that independent audit committee demand for higher quality audit in order to protect their capital reputation as an expert. Contrary to our prediction, this study documents a negative relationship between audit committee expertise and audit fees indicating that auditors perceived firms with more audit committee members that possess accounting and finance expertise to be less risky and thus charged less audit fees to these firms. Furthermore, findings indicate that firms with their own internal audit function pay higher audit fees in comparison to those firms that outsourced their internal audit activities. Consistent with agency theory, the result suggests that the demand for audit services would be lower for firms whose managers own higher percentage of shares due to lower agency cost as compared to those firms with higher outsiders? ownership.